Long-term mortality in patients with atrial septal defect: a nationwide cohort-study - Nyboe, Camilla (Eur Heart J, 2018)
AIMS: In this nationwide cohort of atrial septal defect (ASD) patients, the largest to date, we report the longest follow-up time with and without closure in childhood and adulthood compared with a general population cohort. METHODS AND RESULTS: Using population-based registries, we included Danish individuals born before 1994 who received an ASD diagnosis between 1959 and 2013. All diagnoses were subsequently validated (n = 2277). Using the Kaplan–Meier estimates and Cox proportional hazards regression adjusted for sex, birth year, and a modified Charlson Comorbidity Index, we compared the mortality of ASD patients with that of a birth year and sex matched general population cohort. The median follow-up from ASD diagnosis was 18.1 years (range 1–53 years). Patients with ASD had a higher mortality [adjusted hazard ratio (HR): 1.7; 95% confidence interval (CI): 1.5–1.9] compared with the general population cohort. The adjusted HR 30 days after closure was 1.4 (95% CI: 1.2–1.7), and it was 2.4 (95% CI: 2.0–2.9) for patients without closure. CONCLUSION: Overall, ASD patients had a higher long-term mortality than a general population cohort matched on birth year and gender. Our data indicate a lower relative mortality of those ASD patients undergoing closure than the ASD patients not undergoing closure.